Answer:
C = 1/4
Explanation:
When solving a quadratic equation, there are steps to follow and I'll highlight them here.
Assuming we have an equation
ax² + bx + c = 0
Step 1
If a is not equal to 1, divide all through by a
x² + bx + c = 0
Take c to the other side of the equation
x² + bx = c
Step 2
Add (b/2)² to both sides of the equation
x² + bx + (b/2)² = c + (b/2)²
In our original question,
We had x² + x = 3
a = 1 , b = 1 c = 3
Using step two, we would have
(b / 2)² = (½)² = ¼ (which is the answer)
Now back to the steps
Step 3
We factor our left side of the equation so as to have a perfect square
[x + (b/2)]² = c + (b/2)²
Step 4
Take the square root of both sides of the equation and solve for x
x + b/2 = ±√[c + (b/2)²]
The answer to the question is ¼